COMPARISON OF THE NATIONAL DIAGNOSTIC PAPER-BASED AND ONLINE TESTS IN NATURAL SCIENCE - Juskaite, Loreta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In 2016/2017 Latvian schools were offered the opportunity to choose how to organize the diagnostic test – paper-based or Online. Online tests modernize and facilitate the assessment and analysis process, as well as ensure sustainable elaboration of diagnostic tests and their customization to the new STEM model requirements.  The analysis of the results enables the search for new approaches and methods, for new information systems and technologies in order to enhance certain skills, abilities and attitudes. What is the difference between the results obtained fulfilling tasks in paper-based and online tests? Are there any differences among different ages when conducting paper-based and online tests? The natural science test was conducted among pupils of the 6th grade (11-13 years old).The aim to examine whether the traditional paper-based tests are applicable in a different environment (in an e-environment Online test), whilst maintaining its theoretical and technical specific features and is to focus on the sustainable development of activities in order to improve the quality of education in STEM subjects, which includes using innovative methods in the Latvian educational context.